A novel 3.3 kV 4H-SiC trench PiN with enhanced conductance modulation effect. (1st July 2022) - Zhang, Yourun; Ou, Yanggang; Luo, Jiamin; Wang, Shuai; Zhang, Bo; Niu, Yingxi
Abstract: A novel 3.3 kV rated 4H-SiC trench PiN (T-PiN) structure, which features a trench P+ layer, is proposed and experimentally demonstrated. For the T-PiNs, dry etch onto the N-drift layer is added to the manufacturing process of conventional PiNs (Con-PiNs) before the Al ion implantation step. As the experimental results show, the forward current of the T-PiN diode with an active area of 5 mm × 5 mm has been improved by 32.3% at a voltage of 4 V. Apart from a slight sacrifice in breakdown voltage, the T-PiN is identical to the Con-PiN with regard to other static and surge current capabilities and dynamic characteristics. This superior forward conduction ability of the T-PiNs is a result of enhanced anode carrier injection caused by an enhanced conductance modulation effect and a larger anode carrier injection area. An enhanced conductance modulation effect model was also set up to quantify the increase in the proportion of current density in the T-PiN.